The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jopr.13575
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of implant‐supported monolithic zirconia crowns and fixed partial dentures: A systematic review

Abstract: To determine the survival rates of implant-supported monolithic zirconia crowns and fixed partial dentures (FPD). Material and methods: An electronic search for articles in the English language literature published from January 1, 2001 to September 17, 2021 was performed using PubMed, Scopus, and CENTRAL search engines. After applying predetermined inclusion and exclusion criteria, the definitive list of selected articles was used for calculating the interval survival rate (ISR) and cumulative survival rate (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A 10-year cohort study focusing on implant-supported prostheses revealed slightly higher survival rates in FPDs than SCs (Bragger et al, 2005), and this was coincident with our results. However, recent studies suggested an equal level of survival and complication of these two treatments (Chandran et al, 2022;Kim et al, 2023). To our knowledge, only It is important and meaningful to notice the limitation of this retrospective analysis.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 77%
See 1 more Smart Citation
“…A 10-year cohort study focusing on implant-supported prostheses revealed slightly higher survival rates in FPDs than SCs (Bragger et al, 2005), and this was coincident with our results. However, recent studies suggested an equal level of survival and complication of these two treatments (Chandran et al, 2022;Kim et al, 2023). To our knowledge, only It is important and meaningful to notice the limitation of this retrospective analysis.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 77%
“…A 10‐year cohort study focusing on implant‐supported prostheses revealed slightly higher survival rates in FPDs than SCs (Bragger et al, 2005), and this was coincident with our results. However, recent studies suggested an equal level of survival and complication of these two treatments (Chandran et al, 2022; Kim et al, 2023). To our knowledge, only Boon et al (2020) have evaluated the clinical outcome of different prosthesis types on VTTIs (in the maxillary anterior region), so more well‐designed prospective research should be conducted to estimate the efficacy of VTTIs under different loading types in consideration of many other factors, such as prosthesis materials, abutment types, occlusal design, and masticatory habits.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to the third and multilayered generations, the scientific data evaluating them is scarce, mainly because the multilayer system is the latest release on the market. For predominantly second generation Y-TZP restorations, a recent systematic review has indicated that tooth and implant supported monolithic single crowns presented 96%-100%, and FDPs, 99.6% 3-5 years survival rates, 17,125 with small chippings being the most frequent complication (0.39%). 17 Moreover, monolithic zirconia has also shown to be a feasible alternative to the conventional metal framework for full arch implantsupported prosthesis, achieving 100% survival and success rates after short-term 2 years of follow-up.…”
Section: Polycrystalline Ceramicsmentioning
confidence: 99%
“…3,16 Recent studies have reported excellent short-term (<5 years) survival rates of monolithic zirconia ISFDP; 17,18 however, clinical evidence on the medium-(>5 years) and long-term survival of screw-retained monolithic zirconia ISFDP is still lacking. 19 Consequently, this retrospective study aimed to evaluate the clinical outcomes of screw-retained, ceramicveneered/monolithic zirconia ISFDPs in partially edentulous patients over 5-10 years. Additionally, this study attempted to assess implant-and prosthesis-related factors influencing treatment failure and complications.…”
mentioning
confidence: 99%
“…The survival rate of PFM ISFDP after 5 years was 96.4%, and after 10 years was 93.9% 3,16 . Recent studies have reported excellent short‐term (<5 years) survival rates of monolithic zirconia ISFDP; 17,18 however, clinical evidence on the medium‐ (>5 years) and long‐term survival of screw‐retained monolithic zirconia ISFDP is still lacking 19 …”
mentioning
confidence: 99%